2010
DOI: 10.1007/s11302-010-9178-7
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophils do not express purinergic P2X7 receptors

Abstract: It has been reported that in human neutrophils, external ATP activates plasma membrane purinergic P2X 7 receptors (P2X 7 R) to elicit Ca 2+ entry, production of reactive oxygen species (ROS), processing and release of pro-inflammatory cytokines, shedding of adhesion molecules and uptake of large molecules. However, the expression of P2X 7 R at the plasma membrane of neutrophils has also been questioned since these putative responses are not always reproduced. In this work, we used electrophysiological recordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…Neutrophil accumulation in the skin during croton oil-induced irritant contact dermatitis was reduced in P2X 7 -deficient mice [ 97 ]. However, it was claimed more recently that human neutrophils do not express P2X 7 receptors [ 98 ]. In an RT-PCR study of human neutrophils, mRNA for P2X 1 was strongly expressed, while mRNA for P2X 4 and P2X 5 was weakly expressed and P2X 7 mRNA was not detected [ 99 ].…”
Section: Purinergic Signalling In the Main Subsets Of Immune Cellsmentioning
confidence: 99%
“…Neutrophil accumulation in the skin during croton oil-induced irritant contact dermatitis was reduced in P2X 7 -deficient mice [ 97 ]. However, it was claimed more recently that human neutrophils do not express P2X 7 receptors [ 98 ]. In an RT-PCR study of human neutrophils, mRNA for P2X 1 was strongly expressed, while mRNA for P2X 4 and P2X 5 was weakly expressed and P2X 7 mRNA was not detected [ 99 ].…”
Section: Purinergic Signalling In the Main Subsets Of Immune Cellsmentioning
confidence: 99%
“…The relative amounts of this receptor, however, in these latter cell types in relation to other human hematopoietic cell types remain unknown. Despite the presence of P2X7 on eosinophils, human neutrophils appear to be devoid of P2X7 [26,27]. P2X7 is also present on other human cell types including osteoblasts [28], fibroblasts [29], endothelial cells [30], and epithelial cells residing in various tissues including the skin, cervix, pancreas and colon (see [31,32] and references therein).…”
Section: The P2x7 Receptormentioning
confidence: 99%
“…The expression of P2X7Rs on neutrophils is controversial. Some studies have shown that it is present intracellularly but not on the cell surface (12, 13), whereas one study showed that it has antiapoptotic effects in neutrophils (14). Activation of macrophages is associated with increased expression of P2X7Rs (15).…”
mentioning
confidence: 99%